The discursive construction of Romanian immigration in the British media: Digitized press vs. Television documentaries - Bianca Florentina Cheregi (Romanian Journal of Communications and Public Relations, 2015)
This paper looks at how the media – particularly the British press and television – frames the issue of Romanian immigrants in Great Britain, in the context of the freedom of movement for workers in the European Union. The study focuses on the frames employed by the British journalists in constructing anti-immigration discourses in the digital and the TV sphere, comparatively. This study analyzes the stereotypes about Romanian people used in two British media formats and the way in which they affect Romania’s country image overseas. Using a mixed research approach, combining framing analysis (Entman, 1993) with critical discourse analysis (Van Dijk, 1993), and dispositif analysis (Charaudeau, 2005) this article investigates 271 news items from three of the most read newspapers in the UK (The Guardian, Daily Mail and The Independent), published online during January 2013 – March 2014. Also, the paper analyzes three film documentaries from BBC (Panorama – The Romanians are Coming? – BBC1, The Truth About Immigration – BBC2 and The Great Big Romanian invasion – BBC World News). The analysis shows that the British press and television use both similar and different frames to coverage Romanian migrants. The media also infer the polarization between “Us” (the British media) and “Them” (the Romanian citizens).